The Phenomenon of Scroll, Checkout, Repeat from the Perspective of Hadith: A Thematic Study of the Concept of Israf and Consumption Control - Mohammad Yusuf Zakaria; Vivin Nurfaida; Muhid Muhid (Journal of General Education and Humanities, 2026)
The rapid growth of e-commerce has transformed modern consumption patterns into increasingly instant, spontaneous, and repetitive behaviors, a phenomenon aptly described as "scroll, checkout, repeat." This behavior is no longer driven solely by genuine need. However, it is heavily shaped by digital algorithms, promotional stimuli, lifestyle trends, and emotional impulses such as Fear of Missing Out (FOMO), raising critical questions about the ethical boundaries of consumption from an Islamic perspective. This study aims to analyze the "scroll, checkout, repeat" phenomenon through a thematic study (maudhu'i) of the Prophet's hadith, specifically examining the concepts of israf (excess) and consumption control as ethical frameworks relevant to contemporary digital consumption culture. This study employs a qualitative approach with a library research design, using the thematic hadith method (maudhu'i) as its primary analytical tool. Hadith related to the themes of consumption, israf, tabdzir (wastefulness), qana'ah (contentment), and self-control were collected from primary sources including Sahih al-Bukhari, Sahih Muslim, Sunan at-Tirmidhi, Sunan Ibn Majah, and Musnad Ahmad and systematically analyzed through the stages of data inventory, classification, content analysis, and contextualization The findings reveal that the Prophet's hadith does not prohibit consumption as a fulfillment of human needs, but establishes clear ethical boundaries to prevent it from descending into waste, squandering of wealth, and the servitude of desire. The concept of israf in the hadith operates on three layers: (1) violation of reasonable limits in the use of blessings, (2) desire untrained in contentment, and (3) failure of responsibility toward wealth. Correspondingly, consumption control encompasses: control of measure (sufficiency over appetite), control of attention (abandoning what is not beneficial), and control of inner orientation (cultivating qana'ah). These concepts prove directly relevant to the digital consumption culture of the e-commerce era, where israf no longer manifests as single large expenditures but as small, repetitive, and emotionally driven purchases perpetuated by algorithmic systems. The hadith ultimately offers an ethical solution — grounded in balance, conscious decision-making, and spiritual responsibility — that remains profoundly contextual in addressing contemporary challenges of digital consumption.